Karakteristik Pasien Hipertensi Pada Usia kurang dari 45 Tahun Di Klinik Kimia Farma Pada Juli Tahun 2023 - Aulia, Aidina Trini; Mappahya, AliAspar; Nurhikmawati, Nurhikmawati; Wisudawan, Wisudawan; Ardiansar, Abdul Mubdi (Rumah Sakit Ibnu Sina, Makassar, 2023)
Hypertension is a disorder that occurs in the blood vessels which will result in the intake of oxygen and nutrients below the blood being hampered from reaching the body tissues that need it. Most cases of hypertension in Indonesia occur in the age group 18 years and over with a percentage of 25.80%. The aim of this research is to determine the factors that cause hypertension at ages less than 45 years. This research is quantitative with a descriptive analytical design. Data was collected primarily by interviewing patients and the results were analyzed using SPSS. Research results: In relation to gender with age, occupation, body mass index, family history, and comorbidities, it was shown that women had higher hypertension than men. In addition, most hypertensive patients live in Ujung Pandang and have jobs and comorbidities, thereby increasing the risk of hypertension.